A non-nitric acid method of adipic acid synthesis: organic solvent- and promoter-free oxidation of cyclohexanone with oxygen over hollow-structured Mn/TS-1 catalysts. Issue 3 (2nd February 2015) - Zou, Guoqiang; Zhong, Wenzhou; Mao, Liqiu; Xu, Qiong; Xiao, Jiafu; Yin, Dulin; Xiao, Zisheng; Kirk, Steven Robert; Shu, Tao
Abstract : A novel hollow-structured Mn/TS-1 catalyst has been reported as a non-nitric acid route for adipic acid production from oxidative cleavage of cyclohexanone. Abstract : A novel hollow-structured Mn/TS-1 catalyst has been reported as a non-nitric acid route for adipic acid production from oxidative cleavage of cyclohexanone. The method generates adipic acid in high yields with molecular oxygen under organic solvent- and promoter-free conditions. The hollow nature of the catalyst with large intra-particle voids facilitates the diffusion of bulky molecules to the internal catalytic site and increases the catalyst activity. The advantage of this catalyst is its reusability with almost consistent reactivity, thereby making it viable for industrial applications.